Relationships between Dietary Patterns and Indices of Arterial Stiffness and Central Arterial Wave Reflection in 9-11-Year-Old Children - Pouya Saeedi; Jillian Haszard; Lee Stoner; Sheila Skeaff; Katherine E. Black; Brittany Davison; Harriet Harrex; Kim Meredith-Jones; Robin Quigg; Jyh Eiin Wong; Paula M.L. Skidmore (MDPI AG, 2020)
Arterial stiffness is an important marker of vascular damage and a strong predictor of cardiovascular diseases (CVD). Given that pathophysiological processes leading to an increased arterial stiffness begin during childhood, the aim of this clustered observational study was to determine the relationship between modifiable factors including dietary patterns and indices of aortic arterial stiffness and wave reflection in 9-11-year-old children. Data collection was conducted between April and December 2015 in 17 primary schools in Dunedin, New Zealand. Dietary data were collected using a previously validated food frequency questionnaire and identified using principal component analysis method. Arterial stiffness (carotid-femoral pulse wave velocity, PWV) and central arterial wave reflection (augmentation index, AIx) were measured using the SphygmoCor XCEL system (Atcor Medical, Sydney, Australia). Complete data for PWV and AIx analyses were available for 389 and 337 children, respectively. The mean age of children was 9.7 ± 0.7 years, 49.0% were girls and 76.0% were classified as "normal weight". The two identified dietary patterns were "Snacks" and "Fruit and Vegetables". Mean PWV and AIx were 5.8 ± 0.8 m/s and −2.1 ± 14.1%, respectively. There were no clinically meaningful relationships between the identified dietary pattern scores and either PWV or AIx in 9-11-year-old children.